Search for dark matter produced in association with a bottom-quark in proton-proton collisions at /s=8 TeV with the CMS experiment / Hoh Siew Yan - Hoh , Siew Yan (2017)
Dark Matter is a hypothetical particle proposed to explain the missing matter discovered from the cosmological observation. The motivation of Dark Matter is overwhelming, however those studies mainly deduced from gravitational interaction which does little to understand the underlying structure of the particle. On the other hand, the WIMP Miracle motivating dark matter production at weak scale, implying the possibility of detecting dark matter in LHC. Assuming Dark Matter is the only new particle accessible in LHC, it is expected to be pair produced in association with a Standard Model particles which can be inferred from the Transverse Missing Energy. Search for dark matter in monojet final state is a dominant channel in placing model-independent constrains on a set of effective operators coupling Dark Matter to Standard Model particle. However in the case of effective operators generated by the exchange of heavy scalar mediator, the inclusive Monojet channel is weakened due to the light quark suppression. An exclusive search on heavy quark final state such as bottom quark can improve the coupling strength of the Dark Matter process and reduce significantly the Standard Model backgrounds. A preliminary study on the search for Dark Matter produced in association with a bottom-quark is carried out as an extension to the Monojet search by requiring a b-tagged jet using the data collected by Compact Muon Solenoid detector in proton-proton collisions at center of mass energy of 8 TeV. The study shows that the data is consistent with Standard Model prediction and a limit is derived on the interaction scale and nucleon-dark matter scattering cross section.